2012
DOI: 10.1155/2012/358024
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in the Setting of Hemodialysis Using Biocompatible Membranes

Abstract: Thrombocytopenia is a known potential side effect of hemodialysis, however, it is rarely seen in patients who undergo hemodialysis using biocompatible membranes. This case demonstrates hemodialysis-associated thrombocytopenia with use of biocompatible dialysis membranes that expose blood directly to polysulfone. The thrombocytopenia resolved in this patient when the dialysis membrane was changed to a biocompatible model with a polyethylene glycol barrier layer preventing direct interaction between patient bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Consumption of platelets may be attributed to either an intravascular graft or dialysis catheter, thrombotic microangiopathy caused by hypertensive crisis, or thrombotic thrombocytopenic purpura (37,38). In addition, dialyzer membranes also initiate the complement cascade pathway, platelet adhesion, aggregation, and activation leading to thrombocytopenia (13,39,40). Ng et al (31) also demonstrated that HCV infection was a risk factor (OR = 3.27) for thrombocytopenia in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of platelets may be attributed to either an intravascular graft or dialysis catheter, thrombotic microangiopathy caused by hypertensive crisis, or thrombotic thrombocytopenic purpura (37,38). In addition, dialyzer membranes also initiate the complement cascade pathway, platelet adhesion, aggregation, and activation leading to thrombocytopenia (13,39,40). Ng et al (31) also demonstrated that HCV infection was a risk factor (OR = 3.27) for thrombocytopenia in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Daugirdas et al performed an extensive literature review on the molecular causes of platelet reduction following haemodialysis and concluded that, most recently, cases of dialysis-associated thrombocytopenia were related to the use of polysulfone membranes, especially those sterilised by e-beam 8. There are eight case reports of possible dialysis membrane-related thrombocytopenia, describing the use of e-beam membrane 5 6 9–14. The specific membrane used in each case is not explicitly reported but most cases were attributed to Fresenius membranes from the Optiflux series.…”
Section: Discussionmentioning
confidence: 99%